2020
DOI: 10.1101/2020.10.02.323865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vascular origins of low-frequency oscillations in the cerebrospinal fluid signal in resting-state fMRI: Interpretation using photoplethysmography

Abstract: Slow and rhythmic spontaneous oscillations of cerebral blood flow are well known to have diagnostic utility, notably frequencies of 0.008-0.03 Hz (B-waves) and 0.05-0.15Hz (Mayer waves or M waves). However, intracranial measurements of these oscillations have been difficult. Oscillations in the cerebrospinal fluid (CSF), which are influenced by the cardiac pulse wave, represent a possible avenue for non-invasively tracking these oscillations using resting-state functional MRI (rs-fMRI), and have been used to c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Conversely, the apparent increase in fMRI frequency with age, given the observation that overall fMRI signal fluctuation amplitude decreases with age in both frequency bands, point to a reduced contribution of low‐frequency fluctuations to fMRI in older adults. In the 0.01–0.1 Hz band, the low‐frequency contributions include arterial carbon dioxide (CO 2 ) fluctuations, respiratory variability and heart‐rate variability (HRV) (Attarpour et al, 2021; Chang & Glover, 2009). Very‐low frequency vascular oscillations measured using near‐infrared spectroscopy have been found to decline in amplitude with age (Schroeter, Schmiedel, & von Cramon, 2004) and coincide in frequency with the resting vascular response to arterial CO 2 fluctuations (0.02–0.04 Hz) (Golestani et al, 2015; Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, the apparent increase in fMRI frequency with age, given the observation that overall fMRI signal fluctuation amplitude decreases with age in both frequency bands, point to a reduced contribution of low‐frequency fluctuations to fMRI in older adults. In the 0.01–0.1 Hz band, the low‐frequency contributions include arterial carbon dioxide (CO 2 ) fluctuations, respiratory variability and heart‐rate variability (HRV) (Attarpour et al, 2021; Chang & Glover, 2009). Very‐low frequency vascular oscillations measured using near‐infrared spectroscopy have been found to decline in amplitude with age (Schroeter, Schmiedel, & von Cramon, 2004) and coincide in frequency with the resting vascular response to arterial CO 2 fluctuations (0.02–0.04 Hz) (Golestani et al, 2015; Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The previous work, while extremely novel and informative, has left some unanswered questions. There is still very limited investigation into variations in the frequency of the rs‐fMRI signal in aging and the age–sex interaction. Given the known complexity of the signal and noise contributions to the rs‐fMRI signal, including by intrinsic variations in carbon dioxide (CO 2 ) (Chang & Glover, 2009; Golestani, Chang, Kwinta, Khatamian, & Chen, 2015; Wise, Ide, Poulin, & Tracey, 2004), respiration (Birn, Diamond, Smith, & Bandettini, 2006; Chang & Glover, 2009; Golestani et al, 2015; Shams, LeVan, & Chen, 2021) and cardiac pulsation (Attarpour, Ward, & Chen, 2021; Chang et al, 2013; Falahpour, Refai, & Bodurka, 2013; Shmueli et al, 2007), the neuronal associations of the observed frequency shifts remain unclear. Hence, it is still unclear how EEG and fMRI are related in aging. Given the widespread use of Fourier‐transform based methods for studying rs‐fMRI power distributions (Zou et al, 2008), it is important to clarify whether Fourier‐based spectral decomposition can produce results to support the Hilbert‐transform‐based findings. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CO 2 response has also been reported to exhibit network structure that coincide with that of conventional rs-fMRI functional networks ( Bright et al, 2020 ). Cardiac pulsatility, which entrains the autonomic nervous system, is also known to contribute to the rs-fMRI signal in a spatially specific manner ( Shmueli et al, 2007 ; Chang et al, 2009 ; Shokri-Kojori et al, 2018 ; Attarpour et al, 2021 ). In fact, a substantial portion of the rs-fMRI signal may stem from cardiogenic vascular oscillations, and such signals can interact with respiration and CO2 in a biofeedback loop ( Attarpour et al, 2021 ).…”
Section: The Role Of Cvr In Resting-state Fmrimentioning
confidence: 99%
“…Cardiac pulsatility, which entrains the autonomic nervous system, is also known to contribute to the rs-fMRI signal in a spatially specific manner ( Shmueli et al, 2007 ; Chang et al, 2009 ; Shokri-Kojori et al, 2018 ; Attarpour et al, 2021 ). In fact, a substantial portion of the rs-fMRI signal may stem from cardiogenic vascular oscillations, and such signals can interact with respiration and CO2 in a biofeedback loop ( Attarpour et al, 2021 ). Respiratory and cardiac-related physiological networks have recently been documented in detail ( Chen et al, 2020 ).…”
Section: The Role Of Cvr In Resting-state Fmrimentioning
confidence: 99%